2020
DOI: 10.7554/elife.52648
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin accessibility dynamics and single cell RNA-Seq reveal new regulators of regeneration in neural progenitors

Abstract: Vertebrate appendage regeneration requires precisely coordinated remodeling of the transcriptional landscape to enable the growth and differentiation of new tissue, a process executed over multiple days and across dozens of cell types. The heterogeneity of tissues and temporally-sensitive fate decisions involved has made it difficult to articulate the gene regulatory programs enabling regeneration of individual cell types. To better understand how a regenerative program is fulfilled by neural progenitor cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 87 publications
1
62
0
Order By: Relevance
“…Contrary to the expected, recent high-throughput analysis of the response of pax6-expressing neural progenitor cells to tail amputation showed that before proliferation a set of neural progenitors is directly differentiated into neurons through the activation of a neurogenic program during the first 24 hpa. To replenish the regenerated spinal cord of neural progenitors its proliferation is only triggered at 48–72 hpa [ 64 ]. This immediate differentiation, without a previous proliferative step, probably allows the formation of new neurons very rapidly supporting a successful regenerative process.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the expected, recent high-throughput analysis of the response of pax6-expressing neural progenitor cells to tail amputation showed that before proliferation a set of neural progenitors is directly differentiated into neurons through the activation of a neurogenic program during the first 24 hpa. To replenish the regenerated spinal cord of neural progenitors its proliferation is only triggered at 48–72 hpa [ 64 ]. This immediate differentiation, without a previous proliferative step, probably allows the formation of new neurons very rapidly supporting a successful regenerative process.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of interpreting a snapshot of a cell's gene expression, a chromatin signature can provide information about the cell's prospective state and reveal important insights into the gene regulatory networks at play. Chromatin signatures have already been determined for many types of stem cells [81][82][83][84], and ATACseq is broadly applicable across systems [85].…”
Section: Caveatsmentioning
confidence: 99%
“…With the exception of an mRNA-seq study in lamprey, which demonstrated that the response of brain and spinal cord to SCI indeed differ [ 48 ], previous genome-wide expression studies on spinal cord regeneration have focused on either the spinal cord itself, with the lesion at the epicenter ( Xenopus laevis tadpole and frog [ 70 ], turtle [ 142 ], zebrafish [ 50 ]), or on a regenerating tail (e.g., salamander [ 87 ], Xenopus tropicalis tadpole [ 21 , 55 , 80 , 102 ]). Such regeneration involves not only axon regeneration, but also considerable wound repair and tissue restoration.…”
Section: Introductionmentioning
confidence: 99%